Ograniczenie wolności działalności gospodarczej w drodze rozporządzenia w dobie pandemii COVID-19 - Trela, Anna (Wydawnictwo Uniwersytetu Wrocławskiego, 2022)
The article deals with regulations as the legal basis for introducing restrictions on the freedom of economic activity during the COVID-19 pandemic. The author analyzes the relationship between art. 22 and 31 sec. 3 of the Constitution of the Republic of Poland and indicates the understanding of the terms “restriction” and “reglamentation” of the freedom of economic activity in science and in the judicature.
Keywords: freedom of economic activity; reglamentation; COVID-19; regulation